Ejercicio aeróbico en pacientes con enfermedad arterial periférica. - Camino Espinoza, Nayeli de los Ángeles (2026)
This research analyzes the dissemination of content by the Ecuadorian newspaper El Comercio on the social media platform Instagram from January to June 2022. The study is motivated by the need to understand how traditional media adapt to digital environments and meet audiences’ new information demands, especially those of younger users. The main objective was to analyze the type, frequency, and impact of the content published by El Comercio on Instagram. A mixed-methods approach was applied, combining qualitative techniques such as expert interviews with quantitative methods, including a content analysis of 101 randomly selected posts from an estimated total of 2,100 posts. The findings reveal a predominant use of national and social topics, using formats such as images, memes, and reels. Interactive elements, like the character “Michimercio,” and the strategic use of hashtags helped increase audience engagement. Despite staffing limitations, the outlet has sought to maintain journalistic rigor and adapt its communication to digital norms. The study concludes that El Comercio has established a significant presence on Instagram, although improvements are needed in content originality, visual storytelling, and community-building strategies.